IDENTIFYING THE TRUST RELATIONSHIP BETWEEN EMPLOYERS AND EMPLOYEES: IN THE CONTEXT OF CHINESE ORGANIZATIONS - Law, Kian Aun (International Journal of Psychosocial Rehabilitation, 2020)
Confronting with changeable and volatile business environment, organization entails a rapid growth of the trust relation. In the research of intra-organizational trust, it has become an increasingly remarkable trend to focus on the development of active trust, which marks an effective strategy to strengthen the awareness of trust. In this connection, organization and individual should make its ambition to establish and develop trust instead of recognizing trust process as a passive development as an accumulative result of passing time. This paper, from the dual perspectives of individual behavior characteristics and organizational risk control, makes endeavors to vindicate the inter-level model of trust development within an organization through comprehensive exploration and empirical analysis at the individual and organizational levels so as to promote the initiative of both individuals and organizations to enhance organizational trust atmosphere, and press ahead with the active trust development via confirmed measures.